High hydrostatic pressure processing of beef patties: Effects of pressure level and sodium tripolyphosphate and sodium chloride concentrations on thermal and aggregative properties of proteins - Speroni Aguirre, Francisco José (2014)
Beef patties added with sodium tripolyphosphate (STPP; 0, 0.25 or 0.5%) and/or NaCl (0, 1 or 2%) were treated at 200 or 300 MPa (5 min, 5 °C) or kept refrigerated (non-pressurized). In non-pressurized patties, NaCl solubilized proteins which resulted denatured, whereas STPP solubilized proteins which remained in a native state. At 200 MPa, myosin head was more sensitive to high hydrostatic pressure (HHP) than actin. 1% NaCl favored HHP-induced denaturation of myosin head and actin, whereas 0.25% STPP protected against that effect. At 300 MPa, STPP favored HHP-induced denaturation of myosin head, actin and other proteins. The effect of STPP at 200 MPa may depend on the presence of specific binding sites for STPP anion. These sites would be destroyed due to unfolding at 300 MPa, because of the higher pressure level. No formation of insoluble aggregates occurred at 200 MPa, whereas insoluble aggregates were formed at 300 MPa in samples without salts. Salts minimized protein aggregation observed at 300 MPa. Noticeable differences in thermal and aggregative behavior occurred whether HHP level was 200 or 300 MPa.